Novel Aspects of the Purpose-Built Materials Strategy: Evidence of Topographic Template Effect and Oriented Attachment Growth Mechanism - Leite, Edson R.; Lopes, Kirian P.; Ribeiro, Caue; Orlandi, Marcelo O. [UNESP]; Long, Elson [UNESP] (Amer Scientific Publishers, 2008)
We report two novel aspects relating to the growth of oriented 3D arrays of SnO2 nanorods, based on the "purpose-built materials" (PBM) strategy. Under controlled conditions, the substrate acted as a topographic template and the growth direction of the 3D arrays of SnO2 nanorods was unrelated to the crystallographic characteristic of the substrate. A growth process based on the oriented attachment mechanism was proposed to explain this behavior, and this findings, reported here for SnO2, can be extended to include other metal oxides.
Keywords: Crystal Growth; Thin Films; Semiconductors; Crystalline Oxides; Oriented Attachment